Effectiveness of routine measurement of health-related quality of life in improving the outcomes of patients with musculoskeletal problems—a cluster randomised controlled trial: protocol paper. Issue 12 (15th December 2020) - Lam, Cindy; Chin, Weng Yee; Wong, Carlos King Ho; Or, Kalun; Fong, Daniel Yee Tak; Cheung, Jason Pui Yin; Chao, David Vai Kiong; Wong, Eliza L Y; Kind, Paul
Abstract : Introduction: Managing chronic musculoskeletal problems usually focuses on pain control using medications, but outcomes are often unsatisfactory and sometimes harmful. Information on a patient's health-related quality of life (HRQOL) may trigger a doctor to tailor management improving quality of life. The aim of this trial is to find out whether routine measurement and reporting of a patient's EuroQoL 5-Dimension 5-Level (EQ-5D-5L) HRQOL data using an electronic platform can improve HRQOL and pain in patients with chronic knee or back problems in primary care. We will also assess the acceptability of routine electronic measurements and reporting of the EQ-5D-5L in primary care settings. Methods: This is a multicentre, prospective, cluster randomised controlled trial set in six public primary care clinics in Hong Kong. At the intervention clinics, subjects will complete an electronic EQ-5D-5L form at recruitment and at each clinic follow-up over 12 months. A report of the patient's longitudinal EQ-5D-5L data will be provided to the doctor. Subjects in the control clinics will receive care as usual. All subjects will complete the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), a 10-point Pain Rating Scale and a structured questionnaire to collect sociodemographic information and data on morbidity and service utilisation at recruitment at baseline, 3, 6 and 12 months. Primary outcome is the change in WOMAC total score. Secondary outcomes are change in pain, other patient-reported outcome scores and doctor-rated severity of disease. Group differences in the changes in WOMAC and other outcome scores over time will be analysed using generalised estimating equation model with an intention-to-treat principle. Ethics and dissemination: Ethics approval has been obtained from The University of Hong Kong/Hospital Authority Hong Kong West Cluster (IRB reference number: UW 18-270). The results of the trial will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT03609762 .